Experimental study on the uptake and effects of arsenic originated from poultry litter on the growth of Brassica napus in greenhouse pot cultivation and health risk assessment - Haiyun, Xie; Deming, Han; Cheng, Jinping; Liang, Wang; Pei, Zhou; Wenhua, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Organoarsenics are widely used as growth promoters in poultry industry, resulting in arsenic (As) accumulation in poultry litter. A greenhouse pot study was implemented to investigate the fate of arsenic originated from poultry litter and their effects on the growth of Brassica napus (oilseed rape), and assess their potential health risks. Five poultry litter application rates (0, 5%, 10%, 20% and 40%) were used, dividing into two groups: one for soil incubation (SI) and the other for plant cultivation (PC). Experimental results indicated that the total arsenic for composted poultry litter was (10.94±0.23) mg/kg, As(V) and As(III) decreased while methylated arsenic increased after 21 d in SI and PC treatments. Seed germination rates were negatively correlated with monomethylarsenic acid (MMA, R2=0.63). The length and biomass of roots and shoots were significantly inhibited by poultry litter, but plant length of 5% treatments was slightly stimulated. Within an average weekly intake of 0.5 kg Brassica napuss, the risk quotient (RQ) values induced from roots nearly all surpassed the acceptable limit (1), were two orders magnitude higher than shoots. According to the potential risk to order, child exhibited the highest risk, adolescent ranked secondly, and adult exhibited the lowest risk. Hence, people should better avoid intake Brassica napus roots to reduce arsenic potential risk.Keywords: arsenic uptake, poultry litter, arsenic speciation, pot cultivation experiment, Brassica napus, health risk assessmentDOI: 10.3965/j.ijabe.20160903.2251Citation: Xie H Y, Han D M, Cheng J P, Wang L, Zhou P, Wang W H. Experimental study on the uptake and effects of arsenic originated from poultry litter on the growth of Brassica napus in greenhouse pot cultivation and health risk assessment. Int J Agric & Biol Eng, 2016; 9(3): 186－193.